MAPPING COASTAL VULNERABILITY USING ICVI (INTEGRATED COASTAL VULNERABILITY INDEX) IN NAM DINH COAST, VIETNAM - Hai Hoa, Nguyen; Ngoc Tu Uyen, Bui; Gabriela Flores Montenegro, Diana; Thi Thu Hien, Nguyen; Hoang Vuong, Dang; Thi Bich Hao, Nguyen (Journal of Forestry Science and Technology, 2018)
Based on coastal topographical and geomorphologic features, natural and socioeconomic conditions, 3 groups of indices were selected to assess the coastal vulnerability, including: (i) geographical indices; (ii) eco-environmental indices; and (iii) socio-economic indices. Through surveying in field trip and based on available reports, this study analyzed data and constructed coastal vulnerability maps in Nam Dinh coast. The results showed that the total length of the studied shorelines is 65.62 kilometers, including 17.42 km of coastline with low level of vulnerability (26.55%); 16.73 km with moderate level of vulnerability (25.5%); 14.63 km of coastline with high level of vulnerability (22.3%); and 16.84 km of coastline with a very high level of vulnerability (25.65%). Based on the results, this study proposed 3 main solutions to adapt climate change impacts for vulnerable areas, containing (i) protection; (ii) accommodation; and (iii) retreat.